Nauczanie języka polskiego jako obcego w kontekście interkomprehensyjnej dostępności języków blisko spokrewnionych .......... 255 - Hofmański, Wojciech (70 lat polonistyki Pekińskiego Uniwersytetu Języków Obcych: Dziedzictwo, rozwój, innowacje, 2025)
TEACHING POLISH AS A FOREIGN LANGUAGE IN THE CONTEXT OF INTERCOMPREHENSION OF CLOSELY RELATED LANGUAGES? The article explores the role of the Polish language in the context of Slavic interlingual communicability and emphasizes the significance of the intercomprehensive “seven sieves” technique in Polish studies and, more broadly, in language education for nonnative speakers. The systemic linguistic distance between selected Slavic languages is analyzed as a foundation for presenting the results of studies on the adaptive procedure. Findings and practical applications indicate that contact-based training can effectively enhance interlingual comprehension. A key component of the article is the presentation of the “seven sieves” technique in its variant designed for Slavic languages, illustrated through the example of Czech-Polish relations. This technique can be utilized to develop passive language skills among learners in both Slavic and non-Slavic contexts, particularly at the B2/B2+ level or higher, with a primary focus on reading proficiency. The article underscores the relevance of such methods in the era of artificial intelligence development and highlights their potential for improving the effectiveness of macroregional language education.